Tunnel shields and the use of compressed air in subaqueous works - Copperthwaite, William Charles (Archibald Constable, 1906)
At the time of writing, virtually nothing had been published on the history of shield-work - the employment of a shield, with or without the aid of compressed air, in tunnelling operations of English origin. The author's aim was to gather in one volume a mass of information until then scattered and difficult to find.
Includes index.
Keywords: Tunnel lining.; Underwater construction.; elektronické knihy; electronic books